4f-3d interaction dominated field tailoring spin switching in rare earth doped Dy0.5Er0.5FeO3 single crystal. (June 2021) - Zhao, Gang; Fan, Wencheng; Chen, Haiyang; Ma, Xiaoxuan; Kang, Baojuan; Lu, Wenlai; Zhang, Jincang; Cao, Shixun
Highlights: Spin reorientation transition from Γ4 to Γ2 occurs near 35.9-48 K in Dy0.5 Er0.5 FeO3 single crystal. Co-occurrence of spin switching (magnetization jump in zero-field-cooling mode and magnetization drop in field-cooling modes) is observed. The trigger temperature of the spin switching can be tailored by applied field in a wide temperature range. Antiferromagnetic phase transition peaks are observed in a and c axes at extremely low temperatures. ABSTRACT: A large single crystal Dy0.5 Er0.5 FeO3 of 5.2 mm in diameter and 55 mm in length is prepared using the optical floating zone furnace system. The good quality of the single crystal without impurities is confirmed by powder and Laue X-ray diffraction experiments. Magnetic measurements are conducted using 1 2 millimeter cubic sample of Dy0.5 Er0.5 FeO3 single crystal, which experiences spin switching in two measurement modes of zero-field-cooling (ZFC) and field-cooling (FC) magnetization vs temperature ( M - T ) curves under magnetic fields less than 48 Oe. The co-occurrence of spin switching (i.e. magnetization drop in FC mode and magnetization jump in ZFC mode) has not been reported in the parent materials of DyFeO3 and ErFeO3 single crystals. More interestingly this kind of spin switching can be easily tailored by using low fields in a large temperature range from below 50 K to nearly 400 K. Spin reorientation transition occurs near 35.9-48 K, where the spin configuration of the iron sublattice changes from Γ4 and Γ2 . The magnetic interaction between (Dy, Er)-4 f and Fe-3 d electrons in the two different sublattices of Dy0.5 Er0.5 FeO3 single crystal which governs the spin reorientation transition and spin switching under different temperature and magnetic field are discussed. Graphical abstract: Image, graphical abstract